Agile 2 : the Next Iteration of Agile - Berg, Cliff (John Wiley & Sons, 2021)
Agile is broken. Most Agile transformations struggle. According to an Allied Market Research study, "63% of respondents stated the failure of agile implementation in their organizations." The problems with Agile start at the top of most organizations with executive leadership not getting what agile is or even knowing the difference between success and failure in agile. Agile transformation is a journey, and most of that journey consists of people learning and trying new approaches in their own work. An agile organization can make use of coaches and training to improve their chances of success. But even then, failure remains because many Agile ideas are oversimplifications or interpreted in an extreme way, and many elements essential for success are missing. Coupled with other ideas that have been dogmatically forced on teams, such as "agile team rooms", and "an overall inertia and resistance to change in the Agile community," the Agile movement is ripe for change since its birth twenty years ago. "Agile 2" represents the work of fifteen experienced Agile experts, distilled into Agile 2: The Next Iteration of Agile by seven members of the team. Agile 2 values these pairs of attributes when properly balanced: thoughtfulness and prescription; outcomes and outputs, individuals and teams; business and technical understanding; individual empowerment and good leadership; adaptability and planning. With a new set of Agile principles to take Agile forward over the next 20 years, Agile 2 is applicable beyond software and hardware to all parts of an agile organization including "Agile HR", "Agile Finance", and so on. Like the original "Agile", "Agile 2", is just a set of ideas - powerful ideas. To undertake any endeavor, a single set of ideas is not enough. But a single set of ideas can be a powerful guide.
Keywords: Agile software development.; elektronické knihy; electronic books